A Late Quaternary record of highstand shedding from an isolated carbonate platform (Juan de Nova, southern Indian Ocean). (28th January 2019) - Counts, John W.; Jorry, Stephan J.; Vazquez Riveiros, Natalia; Jouet, Gwenael; Giraudeau, Jacques; Cheron, Sandrine; Boissier, Audrey; Miramontes, Elda
Abstract: A 27 m core collected on the sea floor near Juan de Nova island at 1, 909 m depth in the SW Indian Ocean preserves a high‐resolution record of carbonate sediment export to the deep sea over the past 1 Myr. Core chronology was established using calcareous nannofossil biostratigraphy and benthic foraminiferal δ 18 O. Throughout the core, preserved highstand intervals (MIS 1, 5, 7, 9, 11, 13, 15, 23 and 25) are marked by an increase in the aragonite content within the sediment. Aragonite is likely sourced from the nearby Juan de Nova carbonate platform ca 10 km to the south, and is interpreted as resulting from flooding of the platform top. Platform inundation allows carbonate muds to be winnowed from their original shallow‐water environment of deposition, suspended in the water column, and redeposited onto the proximal slopes and within the basin. Sharp increases in aragonite content at the beginning of each highstand interval can be used to estimate the approximate sea‐level range when platform flooding occurred; results show that the depth of the platform top has likely changed little over the past 1 Myr due to balanced aggradation and subsidence. Previously hypothesized large‐scale aragonite dissolution cycles are evidenced by a disproportionally low aragonite increase during MIS 11. This study provides a new, exceptionally long record of highstand shedding, expanding the known occurrences of the process to the southern Indian Ocean and supporting its importance as a globally significant depositional mechanism that impacts deep‐sea stratigraphic records. Abstract : A core from the deep ocean near Juan de Nova platform shows a correlation between aragonite content and sea‐level across multiple Late Quaternary glacial–interglacial cycles. This relationship is interpreted as being caused by increased production and export of carbonate on the flooded platform top during times of high sea‐level.